Proyecto de factibilidad para la creación de una empresa productora y comercializadora de vino de naranja en el cantón Puyango - Granda Farfán, Víctor Ángel (2016)
The overall objective of this research work is to "determine the feasibility of creating a producer and marketer of orange wine in the canton Puyango". As has developed a feasibility project for the implementation of this type of business, such as an urgent need to meet the demand for this product has a high percentage of households host city Alamor Region Puyango province Loja. With the above background, the study of the existing market demand for this product was determined that the zero year or year of study the potential demand is 3880, and 3570 have actual demand, effective demand in 3498 and expected demand of 92462 . Subsequently, the annual supply is 5340 is obtained and then the unsatisfied demand is 87122 is obtained. Technical Study on the optimum size of the project, whose installed capacity is 48,000 bottles of wine and capacity utilization 38400 was established, that because the company was established and there is business inexperience. The location of the company it was determined that the most appropriate option according to the array weights corresponds to M Street and O, industry Also the distribution of the plant was determined, which will have a good atmosphere in harmony with nature from work. In the organizational structure necessary people for administration and production area was determined. Likewise, the organizational structure was established, the constitution of the company as a stock corporation, where also the minutes of such constitution is included and this part is finished with manual functions for all the people who work in that company . In the financial study it found that the total fixed assets is USD. Deferred assets USD 93,076.78. 1367.10; current assets and USD. Giving a total of 12,984.20 USD. 107,428.07; This initial amount to be financed as follows; the 44.15% of the contributing partners and the rest is the 55.85% who were 60,000.00 will be financed with a loan from the National Finance Corporation. The financial evaluation was determined that the net present value is positive is USD. 113.788,91; the internal rate of return is 30.53% and according to the comparison, is higher than the rate of opportunity cost of capital of 10%; the cost-benefit ratio indicates that for every dollar invested 0.25 cents of return will be achieved, the investment will pay off in 3 months and 2 months and 16 days; finally in the sensitivity analysis it shows that the project, with the increased costs that can endure for positive net flows is 3.50% and the maximum rate on the decline in revenues that will withstand is 3, 00%. Considering the results, the conclusions of the feasibility of implementing a producer of orange wine was ratified.